El nacionalismo juvenil platense y la formación de la Concentración Nacional Universitaria (CNU), 1960-1971 - Juan Luis Carnagui (Centre de Recherches sur les Mondes Américains, 2013)
This article analyzes the emergence and first steps developed by the Concentración Nacional Universitaria between the early 60s and 70s. With a leading role in the peronist’s internal conflicts during the seventies, the CNU had originated in the city of La Plata around 1965. We will analyze, firstly, the different experiences and articulations developed by nationalist youth in this city that enabled the emergence of the organization. Subsequently, we will focus the actions taken by the CNU that allowed the consolidation and growth of the founder group. The documentation of the former Dirección de Inteligencia de la Policía de la Provincia de Buenos Aires, the periodical press of the period, and the literature related to the subject, are the elements with which we propose to reconstruct part of this experience.